Federalism and education : ongoing challenges and policy strategies in ten countries - Wong, Kenneth K., 1955-; Knüpling, Felix; Kölling, Mario; Chebenova, Diana (Emerald Publishing Limited : Information Age Publishing, INC., 2018)
"The balance of centralization and decentralization also varies across institutional and policy domains, such as the legislative framework for education, drafting of curricula, benchmarking for accountability, accreditation, teacher training, and administrative responsibilities at the primary, secondary, and tertiary levels. Given these critical issues in federalism and education, this volume examines ongoing challenges and policy strategies in ten countries, namely Australia, Austria, Belgium, Canada, Germany, Italy, Spain, Switzerland, United Kingdom, and the United States. These chapters and the introductory overview aim to examine how countries with federal systems of government design, govern, finance, and assure quality in their educational systems spanning from early childhood to secondary school graduation. Particular attention is given to functional division between governmental layers of the federal system as well as mechanisms of intergovernmental cooperation both vertically and horizontally. The chapters aim to draw out comparative lessons and experiences in an area of great importance to not only federal countries but also countries that are emerging toward a federal system" -- Provided by publisher.
Keywords: Education and state -- Cross-cultural studies.; Education and globalization -- Cross-cultural studies.; Schools -- Decentralization -- Cross-cultural studies.; Law -- Educational Law & Legislation.; Education law.; elektronické knihy; electronic books